2022
DOI: 10.1186/s41935-022-00278-2
|View full text |Cite
|
Sign up to set email alerts
|

Technology facilitated sexual violence: a comparative study between working and non-working females in Egypt before and during the COVID-19 pandemic

Abstract: Background During the COVID-19 pandemic, quarantine measures policies increased Internet usage, leading to technological hazards as technology facilitated sexual violence (TFSV). Aim The current work aimed to assess TFSV among working and non-working Egyptian females before and during COVID-19. Methods The current work is a cross-sectional observational comparative study using an anonymous online quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 27 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Several studies found that victim-survivors did not report their experiences to the police (Koirala, 2020;Makinde et al, 2021;Sambasivan et al, 2019). In contrast, a study by Zagloul et al (2022), found a small number, 3.9% of respondents (n = 283), reported the incident to the police. However, survivors who reported the incident also noted that they preferred to keep it secret (Alsawalqa, 2021).…”
Section: Coping Strategies and Help-seeking Behaviormentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies found that victim-survivors did not report their experiences to the police (Koirala, 2020;Makinde et al, 2021;Sambasivan et al, 2019). In contrast, a study by Zagloul et al (2022), found a small number, 3.9% of respondents (n = 283), reported the incident to the police. However, survivors who reported the incident also noted that they preferred to keep it secret (Alsawalqa, 2021).…”
Section: Coping Strategies and Help-seeking Behaviormentioning
confidence: 98%
“…Gender Tandoc et al, 2021;Zagloul et al, 2022). A meme is an image, video, or piece of text that is intended to be sexuallyhumorous and which is copied and spread rapidly by internet users, often with slight variations.…”
Section: Types and Patterns Of Tfsva In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at cyber violence as a form of VAW during the pandemic, a recent study found that almost 25% of respondents frequently observed different forms of cyber violence against women and girls ( 13 ). While cyber violence against women significantly increased during the pandemic ( 14 ), there were few rigorous studies on the relationship between the COVID-19 pandemic and VAW. Data from those studies consisted mostly of articles published in comments, editorials, and letters from social media, the Internet, and helpline reports.…”
Section: Shadows Of the Pandemic: Cyber Violence And Suicidementioning
confidence: 99%
“…In their research, many are motivated to prevent or deter such criminal behaviours. Numerous studies have introduced interdisciplinary perspectives that include the psychological, social, medical, and legal components of SHCs (Blackstone et al, 2009; Burn, 2019; Foote, 2016; Lacks et al, 2022; Pryor et al, 1993; Zagloul et al, 2022).…”
Section: Introductionmentioning
confidence: 99%